Urban Morphological Analysis of Rappocini District in Makassar, Indonesia: A Spatial Perspective - Saragi, Alexander Adrian (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study explores the spatial development of Rappocini District in Makassar, Indonesia, through the framework of urban morphology. Utilizing Roger Trancik’s urban design approaches, specifically the figure-ground and linkage methods, the research investigates the district’s land use distribution, building configurations, and circulation systems. The analysis reveals a predominantly angular figure-ground pattern, marked by dense, irregular building masses and minimal open space, indicative of organic, uncoordinated urban expansion influenced by functional and social factors. The linkage structure is dominated by a Mega-Form pattern, where a few primary arterial roads act as the main conduits for movement and connectivity within the area. These spatial characteristics underscore both the complexity and limitations of high-density urban development in the absence of comprehensive planning. The findings contribute to a better understanding of local morphological dynamics and offer valuable insights for guiding context-sensitive and sustainable urban design strategies aimed at improving spatial coherence, accessibility, and quality of life.